REORIENTATION OF ISLAMIC PHILOSOPHICAL TRADITION: AN EPISTEMOLOGICAL ANALYSIS OF THE PERSPECTIVES OF ‘ĀBID AL-JĀBIRĪ AND ḤASAN ḤANAFĪ - Baihaqi, Muhammad Nasrudin (Sekolah Tinggi Agama Islam Sadra, 2025)
Islamic philosophy, which once experienced a golden age, now faces a crisis of innovation characterized by stagnation, repetition, and an inability to respond to contemporary human problems. This condition is often seen as a result of the decline of philosophy after Ibn Rushd, but in fact it is more related to the inappropriate method of reading tradition (turāth) with two main axes: traditionalism/Salafism and liberalism-modernism. This article examines the thoughts of two very important modern Arab figures, ‘Ābid al-Jābirī and Ḥasan Ḥanafī, who both attempted to offer new ways of reading turāth to revitalize Islamic philosophy. The aim is to reveal the relevance of their methods in addressing intellectual stagnation while pointing to a new direction for the Islamic philosophical tradition to remain relevant and productive. This study uses a qualitative method based on content analysis of the main works of ‘Ābid al-Jābirī and Ḥasan Ḥanafī on tradition and renewal. The results of the study show that al-Jābirī, through structural, historical, and ideological criticism, attempts to liberate tradition, especially philosophical texts, from analogical reading (qiyās) and encourages a rationality of tradition that is more in line with the guidance of modernity. Meanwhile, Ḥasan Ḥanafī, through phenomenological hermeneutics, views tradition as an ideological force that must be revived in order to support emancipation and social transformation. Although their points of emphasis differ, both assert that Islamic philosophy can only regain its vitality through a reorientation of tradition so that it remains relevant and capable of responding to the needs of the times.